Krótka historia polskiego sformalizowanego konstytucjonalizmu - Ławniczak, Artur (Wydawnictwo Uniwersytetu Wrocławskiego, 2016)
Polish constitutionalism already has a sufficiently long history. Sensu largo its beginning comes with the birth of the Polish state, because in the material sense constitution means a form of government. In the case of our state we can observe the evolution of the political system from patrimonial monarchy to noble democracy. In this phase of our history it is easy to find any juridical acts known as constitutions such as for example the Nihil novi constitution — the juridical foundation of limited monarchy. In the final years of I Rzeczpospolita Commonwealth we see the so-called Constitution of May 3, but in the reality the name of this legal act was the governmental law.So the first complete constitutional act in our history was the Constitution of the Duchy of Warsaw, which was created by Napoleon in 1812. In 1815 Tsar Alexander I was the donator of the Kingdom of Poland and its Constitution. The latest example of our monarchical Carta Magna was the Act of November 5 — the renewal of the Kingdom of Poland on the part of German and Austrian emperors.In 1921 Poland was already a republic with its own democratically written Ius Supremum. The Constitution from this year has democratic slogans, but later the ideological climate in Europe changed in the direction of the authoritative paradigm. One of the effects of this tendency was the Polish Constitution of 1935.After the Second World War our country became the people’s democracy with juridical foundation in the form of the Constitution of 1952. In 1976, as a result of the change in the official Highest Law Poland entered the socialist democracy, annihilated from the legalsphere by the amendment of 1989, which declared “democracy without an adjective”. Finally in 1997 there appeared the new Constitution as the juridical confirmation of a democratic state of law.
Keywords: Polska; historia; konstytucja; konstytucjonalizm; forma rządu